2018
DOI: 10.3346/jkms.2018.33.e323
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Anticoagulation and Treatment Satisfaction in Patients with Non-Valvular Atrial Fibrillation Treated with Vitamin K Antagonist: Result from the KORean Atrial Fibrillation Investigation II

Abstract: BackgroundVitamin K antagonist (VKA) to prevent thromboembolism in non-valvular atrial fibrillation (NVAF) patients has limitations such as drug interaction. This study investigated the clinical characteristics of Korean patients treated with VKA for stroke prevention and assessed quality of VKA therapy and treatment satisfaction.MethodsWe conducted a multicenter, prospective, non-interventional study. Patients with CHADS2 ≥ 1 and treated with VKA (started within the last 3 months) were enrolled from April 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Existing studies concluded patients from western countries had better TTR than their Asian counterpart. (27) Therefore, the lower mean TTR and the fewer good TTR among patients in this study were similar to other Asia studies. The possible explanations for this variation include Asian may have different diet and genetic, such as polymorphisms of VKOR1 and CYP2C9 genes.…”
Section: Treatment Satisfactionsupporting
confidence: 89%
“…Existing studies concluded patients from western countries had better TTR than their Asian counterpart. (27) Therefore, the lower mean TTR and the fewer good TTR among patients in this study were similar to other Asia studies. The possible explanations for this variation include Asian may have different diet and genetic, such as polymorphisms of VKOR1 and CYP2C9 genes.…”
Section: Treatment Satisfactionsupporting
confidence: 89%
“… 18 , 19 Satisfaction with treatment convenience was reported the lowest (mean score 57) among all TSQM domains in this study which is similar to that reported by patients with AF treated with vitamin K (58), and slightly lower than the mean score (63) reported by patients with PMO. 18 , 19 Surprisingly, satisfaction with treatment convenience in our study was remarkably lower than that reported in patients with haemophilia using PDC syringes in Italy. 20 …”
Section: Discussionsupporting
confidence: 79%
“…Regarding patients’ or caregivers’ satisfaction with treatment, considerably higher satisfaction was reported in three of the TSQM domains, effectiveness (mean score 65), side effects (98) and global satisfaction (67), compared with treatment satisfaction reported in previous studies on other chronic diseases in Korea. 18 , 19 In previous studies using the TSQM, patients with postmenopausal osteoarthritis (PMO) reported treatment satisfaction as 56 in effectiveness, 64 in side effects and 54 in the global domain, and patients with atrial fibrillation (AF) treated with vitamin K scored their treatment satisfaction as 58, 58 and 56 for the TSQM domains of effectiveness, side effects and global satisfaction, respectively. 18 , 19 Satisfaction with treatment convenience was reported the lowest (mean score 57) among all TSQM domains in this study which is similar to that reported by patients with AF treated with vitamin K (58), and slightly lower than the mean score (63) reported by patients with PMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that NOACs, regardless of dosage, may provide better clinical outcomes in patients with AF for whom warfarin is indicated. Poor INR control and low treatment satisfaction of VKA users among Korean patients with AF might be one of the potential underlying reasons for the observed differences in outcomes between warfarin and reduced-dose NOACs in this study [34]. In another study evaluating the effectiveness and safety of NOACs versus warfarin among the Korean population with AF, NOACs had an overall favorable clinical benefit compared to that of warfarin, although 50-75% of the cohort included patients on reduced-dose NOAC treatment [17].…”
Section: Discussionmentioning
confidence: 83%